Response to selection of growth traits in Aceh cattle - Putra, Widya Pintaka Bayu; ., Sumadi .; Tety, H .; Hendra, S. . (Indonesian Journal of Animal and Veterinary Sciences, 2014)
This research aimed to find out the genetic progress for Aceh cattle by several growth traits selection such as birth weight (BW), weaning weight (WW), yearling weight (YW), mature weight (MW) of does to identify the best selection response from bulls and cows breeding patterns. The recorded data of production and reproduction of Aceh cattle from 2010 to 2014 at breeding centre were analyzed and used as a technical coefficient on estimate heritability (h2), genetic correlation (rG), direct selection response (RY) and correlated selection response (CRY) on several breeding patterns. Most ofÂ  h2 and rG value among growth traits were positive and high. The highest value of Ry found on BW (0.04), WW (1.21), YW (2.05), MW (3.28) and this was obtained on breeding pattern for 3 years and cow for 6 years. The indirect selection or CRY value based on BW were lower than WW. It is concluded that WW might be used as selection criterion in order to increase WW, YW and MW. Key Words: Aceh Cattle, Growth Traits, Heritability, Genetic Correlation, Selection Response